Palladium interstitial implant in combination with external beam radiotherapy and chemotherapy for the definitive treatment of a female urethral carcinoma - Hilary P. Bagshaw; Ned L. Williams; Y. Jessica Huang; Jonathan D. Tward; David K. Gaffney (Elsevier, 2015)
Primary urethral cancer is a rare diagnosis, especially in females. This report presents the utilization of a palladium interstitial implant and a review of the retrospective data published on the management of female urethral cancer. Excellent local control and survival has been obtained with the use of a palladium interstitial implant in combination with external beam radiotherapy and concurrent chemotherapy. This modality represents a novel and effective way to treat primary urethral cancer in females.